Developmental Exposure to Endocrine Disrupting Chemicals and Its Impact on Cardio-Metabolic-Renal Health - Singh, Radha Dutt; Koshta, Kavita; Tiwari, Ratnakar; Khan, Hafizurrahman; Sharma, Vineeta; Srivastava, Vikas (Frontiers in Toxicology, 2021)
Developmental origin of health and disease postulates that the footprints of early life exposure are followed as endowment of risk for adult diseases. Epidemiological and experimental evidences suggest that adverse fetal environment can affect the health of offspring throughout their lifetime. Exposure to endocrine disrupting chemicals (EDCs) during fetal development can affect the hormone system homeostasis resulting in broad spectrum of adverse health outcomes. In the present review, we have described the effect of prenatal EDCs exposure on cardio-metabolic-renal health using the available epidemiological and experimental evidences. We also discuss the potential mechanisms of their action which include epigenetic changes, hormonal imprinting, loss of energy homeostasis and metabolic perturbations. The effect of prenatal EDCs exposure on cardio-metabolic-renal health a complex condition of altered biological landscape can be further examined in case of other environmental stressors with similar mode of action.